The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11747-007-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Retail patronage behavior and shopper typologies: a replication and extension using a multi-format, multi-method approach

Abstract: The continuous interaction between retailers and their consumers has fascinated researchers for more than 50 years and has spurred the development of many measurement instruments. While a number of shopper typologies have been proposed, these studies have tended to employ dissimilar measures, samples and retail formats. As a result, the comparability and generalizability of findings are problematic. Using a multi-method, multi-format approach, this study replicates and extends past research findings to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 29 publications
2
89
0
6
Order By: Relevance
“…Likewise, it has been observed that this class of motivations may favour repeat visits to the establishment (Ganesh et al, 2007;Kim et al, 2007;Koufaris et al, 2001), the development of favourable attitudes towards online purchasing, as well as a greater purchase intent (see : Childers et al, 2001;Li et al, 2001). Furthermore, it should be considered that online consumers are inclined to use the internet in search of enjoyment by means of games, online chats, and other forms of entertainment (Swinyard and Smith, 2003).…”
Section: Intrinsic Enjoymentmentioning
confidence: 99%
“…Likewise, it has been observed that this class of motivations may favour repeat visits to the establishment (Ganesh et al, 2007;Kim et al, 2007;Koufaris et al, 2001), the development of favourable attitudes towards online purchasing, as well as a greater purchase intent (see : Childers et al, 2001;Li et al, 2001). Furthermore, it should be considered that online consumers are inclined to use the internet in search of enjoyment by means of games, online chats, and other forms of entertainment (Swinyard and Smith, 2003).…”
Section: Intrinsic Enjoymentmentioning
confidence: 99%
“…Resulta crucial que los responsables de acometer la gestión comercial tengan muy en cuenta esta satisfacción, ya que al constituir una respuesta afectiva a la valoración de atributos del establecimiento comercial -cuya síntesis genera la imagen del establecimiento comercial (Theodoridis y Chatzipanagiotou, 2009)-, los consumidores la utilizan para distinguir unos establecimientos de otros (e.g., Ganesh, Reynolds y Luckett, 2007;Gómez et al, 2004). Además, la satisfacción es un antecedente de las dimensiones críticas del marketing como lo son el compromiso (e.g., Johnson et al, 2001), la lealtad (e.g., Sivadas y Baker-Prewitt, 2000) o la retención de clientes (e.g., Rust y Zahorik, 1993).…”
Section: Marco Conceptualunclassified
“…Al respecto, Gómez et al (2004), Berné (2006) y Ganesh et al (2007), entre otros, identifican diversos atributos del establecimiento comercial que, utilizados adecuadamente por los comerciantes en sus estrategias de diferenciación, son susceptibles de influir positivamente en la satisfacción de los consumidores. Entre estos atributos, cabe mencionar la atención al cliente, aspecto que resulta de gran relevancia especialmente para aquellos grupos de consumidores que disfrutan llevando a cabo procesos de socialización durante el acto de compra (e.g., Tauber, 1972).…”
Section: Marco Conceptualunclassified
See 1 more Smart Citation
“…Even if customer patronage behavior is surely not a new topic in service marketing literature (Tagashira and Minami, 2016) it is still considered a central strategy for being successful in service industries (Darian, Wiman, and Tucci, 2005;Ganesh, Reynolds and Luckett, 2007;Zolfagharian and Paswan, 2009). Moreover, it represents a major concern for managers because it enables them to identify and target those consumers most likely to purchase (Pan andZinkhan, 2006, Patney, 2010).…”
Section: Introductionmentioning
confidence: 99%